Acute Hydrops with Total Corneal Edema in a Very Young Child with Keratoconus: The Youngest Age Reported Case. (12th August 2022) - Sedaghat, Mohammad-Reza; Momeni-Moghaddam, Hamed; Belin, Michael W.; Savardashtaki, Maryam; Naroo, Shehzad A.; Robabi, Hassan
Abstract : Purpose . To present the youngest age ever reported for acute corneal hydrops with total corneal edema in a child with advanced bilateral keratoconus. Methods . Patient presentation in ophthalmic clinic. The patient underwent various clinical tests and examinations including anterior segment optical coherence tomography (AS-OCT) and Scheimpflug corneal tomography. Results . A 5-year-old girl presented with uncorrected distance visual acuity (UDVA) of 0.4 in the right eye and nonmeasurable UDVA associated with severe photophobia in her left eye of a 3-day duration. Intraocular pressure using the iCare tonometer was 14 and 5 mmHg in the right and left eyes, respectively. An old corneal hydrops scar and posterior subcapsular cataract (PSC) in the right eye and a total limbus to limbus corneal hydrops in the left eye were observed on slit-lamp examinations. Scheimpflug corneal tomography was possible in the right eye but, due to excessive irregularity and scaring, was not possible in the left eye. Corneal thinning and scarring were evident in the anterior segment optical coherence tomography in the right eye and very edematous cornea associated with stromal cleft and epithelial bullae in the left eye. A management plan consisting of topical hypertonic solution and ointment was started to reduce her symptoms. Conclusion . Acute corneal hydrops may be the presenting sign of keratoconus; however, extensive hydrops involving the total cornea area at a very young age is very rare and has not been previously reported in the literature.